Survei Indeks Massa Tubuh dan Daya Tahan Kardiovaskular (VO₂MAX) Peserta Ekstrakurikuler Futsal Sekolah Menengah Atas - Aldi Tio Fanny; Hariyoko Hariyoko (LPPM Politeknik Pratama, 2024)
Futsal is a sport that is included in the physical activity category of dynamic sports. To produce quality players, one must pay attention to body mass index, because futsal is a sport that involves direct physical contact. Cardiovascular endurance and body mass index are equally important for futsal players. Based on this explanation, body mass index and cardiovascular endurance are important things to understand to support performance and as assessment instruments. The aim of this study was to assess the cardiovascular endurance and body mass index of futsal extracurricular players of Public High School 8 Malang. In this research, researchers used quantitative descriptive research with survey methods and a cross-sectional approach. The subjects of this research were 30 futsal extracurricular participants who were active of Public High School 8 Malang. The instrument used in this research is a test. When the test is carried out, all forms of activities and actions are recorded and documented. The tests used include measuring body mass index and the Multistage fitness test. The average cardiovascular endurance of the futsal extracurricular participants of Public High School 8 Malang was (46.66%) included in the very poor category, and the average body mass index of the participants (73.33%) was included in the ideal weight category based on the measurement results. which is obtained. Therefore, it can be said that even though cardiovascular endurance is in the very poor category, the body mass index is in the ideal body weight range.